EFEKTIFITAS PEMBERIAN DOSIS PUPUK KANDANG KANDANG KAMBING DAN PUPUK KANDANG SAPI TERHADAP PERTUMBUHAN DAN HASIL TANAMAN BAWANG MERAH - Hafiza, Sularmi; Rizky Septika Utami; Haryuni; Eko Fransisko (PUCUK : Jurnal Ilmu Tanaman, 2023)
One of the important plant cultivation techniques in an effort to increase optimal shallot production is fertilization. Fertilizers provide plants with nutrients that are lacking in the soil. If one of the nutrients needed is lacking, plant growth will suffer and crop yields will decrease. Fertilizer application on shallot plants can use organic fertilizers, this type of fertilizer can meet the needs of shallots for macro and micro nutrients. The materials used in this study were: Batu Hijau red onion, goat manure, cow manure. Research methods This study used a Complete Randomized Block Design (RAKL), with 6 treatment levels. K0: Cow manure 0 tons/ha (polybag) + Goat manure 0 tons/ha (0 g/polybag), K1: Cow manure 0 tons/ha (0g/polybag) + Goat manure 12.5 tons/ ha (62.5g /polybag), K2:Cow manure 0 tons/ha (0g/polybag) + Goat manure 25 tons/ha (125g /polybag), K3:Cow manure 10 tons/ha (50g/polybag) )+Goat manure 0 tons/ha (0g/polybag), K4:Cow manure 10 tons/ha (50g/polybag)+Goat manure 12.5 tons/ha (62.5g/polybag), K5:Manure cowshed 10 tons/ha (50g/polybag) + goat manure 25 tons/ha (125g/polybag). Analyzed using the Anova test, further tested with the LSD test (Less Significant Difference) at the 5% level. Based on the results of the analysis of the smallest significant difference (LSD) test, it showed that 2.5 tons/ha of goat manure produced the highest number of leaves, namely 36 leaves.